Influence and Inheritance in Feminist English Studies
VIII, 96 p.
Keywords: This collection explores how new directions in feminist literary study might be informed by the work of the past. It offers a snapshot view of new feminist research in the field today and traces the influence of the substantial feminist inheritance in English Studies through six distinct, individual pieces of rigorous and innovative new work.